Silicon-based negative electrode material, negative electrode plate and lithium ion battery

By introducing porous silicon, carbon clad layer and bucky paper layer structures into the silicon-based anode material, the problem of excessive volume expansion of the silicon-based anode material in lithium-ion batteries is solved, and higher cycling performance and energy density are achieved.

CN119812241APending Publication Date: 2025-04-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411804833.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The silicon-based negative electrode material is prone to pulverization and inactivation during charging and discharging of lithium-ion batteries, resulting in excessive volume expansion, reduced first effect, rapid attenuation of battery capacity, and poor circulation performance.

Method used

The silicon-based negative electrode material structure is composed of porous silicon, carbon clad layer and Bucky paper layer. The Bucky paper layer provides protection and conductivity as the outermost layer, alleviates the volume expansion effect of silicon, and enhances the stability and cycling performance of the material.

Benefits of technology

Through the porous mesh structure and conductivity of the Bucky paper layer, the volume expansion of silicon is effectively alleviated, the stability of the protective layer on the silicon surface is enhanced, and a stronger SEI film is formed, which improves the circulation performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812241A_ABST
    Figure CN119812241A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a silicon-based negative electrode material, a negative electrode plate and a lithium ion battery. The structure of the silicon-based negative electrode material comprises porous silicon, a carbon coating layer coating the porous silicon and a Bucky paper layer coating the outer surface of the carbon coating layer. Wherein the porous net structure and the conductivity of the Bucky paper are beneficial to the transmission of lithium ions and electrons, and the good flexibility provides a space for the expansion of silicon, so that the volume effect of silicon is reduced, and the expansion of a battery cell in the circulation process is inhibited. Compared with a carbon nanotube, the Bucky paper has the advantages of uniform thickness, stronger stretchability, stronger flexibility, difficult fracture and better inhibition of silicon expansion. When the negative electrode material is used for preparing a negative electrode plate, the compaction density of the negative electrode plate can be improved, the overall thickness of a battery cell is reduced, and the energy density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a silicon-based negative electrode material, a negative electrode sheet and a lithium-ion battery. Background Art

[0002] Nowadays, silicon-based negative electrode materials have the advantages of extremely high theoretical specific capacity, low voltage platform and abundant sources, and have been widely explored as the next generation of high-performance lithium-ion battery negative electrode materials. The application of silicon-carbon systems in consumer batteries and power batteries has begun to be realized.

[0003] However, silicon-based negative electrode materials are easily crushed and inactivated during the charge and discharge process of lithium-ion batteries, resulting in excessive volume expansion and reduced initial efficiency, which in turn leads to many problems such as rapid battery capacity decay and poor cycle performance, greatly affecting large-scale applications.

[0004] Therefore, it is necessary to develop a silicon-based negative electrode material that can solve the problem of cyclic expansion. Summary of the invention

[0005] The purpose of the present invention is to provide a silicon-based negative electrode material to solve the problem of excessive volume expansion of the existing silicon-based negative electrode material in view of the deficiencies in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A silicon-based negative electrode material, the silicon-based negative electrode material structure comprises porous silicon, a carbon coating layer coating the porous silicon and a buckypaper layer coating the outer surface of the carbon coating layer.

[0008] Among them, porous silicon is located in the center layer of the silicon-based negative electrode material structure, which alleviates its volume expansion during the charging and discharging process. The carbon coating layer improves the conductivity of the material and can effectively prevent the electrolyte from diffusing into the silicon microspheres.

[0009] Buckypaper is composed of disordered carbon nanotubes of a certain length. Compared with conventional carbon nanotubes, it has uniform thickness, stronger stretchability, stronger elasticity, will not break easily, has a larger specific surface area, and has strength similar to that of thermally conductive graphite sheets, good electrical and thermal conductivity, and chemical stability. The buckypaper layer will better alleviate the volume expansion effect of silicon, so that the silicon-carbon layer will not break the buckypaper layer and react with the electrolyte when expanding and contracting. This structure enhances the stability of the protective layer on the silicon surface, more effectively ensures the integrity of the silicon-carbon negative electrode, can form a more solid SEI film, and improve the cycle performance of the battery. The buckypaper layer, as the outermost layer, plays a role in protecting the entire structure, and the porous mesh structure and conductivity of buckypaper are conducive to the transmission of lithium ions and electrons. The good softness provides space for the expansion of silicon, reduces the volume effect of silicon, and inhibits the expansion of the battery cell during the cycle. This structure provides space for the expansion of silicon-based materials in the later cycle, effectively improving the problem of cyclic expansion of silicon-based materials.

[0010] Preferably, the buckypaper comprises one or more of carbon nanotube paper, carbon nanofiber paper, and carbon nanotube / fiber hybrid paper.

[0011] Preferably, the tube diameter of the buckypaper is 60-150nm. If the diameter of the buckypaper tube is too small, it is easy to form an overly dense network structure, which has a certain impact on the transmission of lithium ions and electrons. If it is too large, it will have less restraining force to alleviate expansion. If the diameter of the buckypaper tube is less than 60nm, the buckypaper film formed will be too thin to form a coating, and it will not be able to restrain the silicon-based expansion. If the diameter of the buckypaper tube is greater than 150nm, it will affect the energy density and cycle performance of the battery cell.

[0012] Preferably, the thickness of the buckypaper is 600-4500 nm. The preferred range is 600-1200 nm. When the thickness is too large, it has a strong impact on the softness and is not conducive to overmolding.

[0013] Preferably, the thickness of the buckypaper is H, the thickness of the carbon coating layer is d, and the ratio of the buckypaper thickness H to the carbon coating layer thickness d is (20-160):1.

[0014] When the ratio of buckypaper thickness H to carbon coating thickness d exceeds the set range, the buckypaper layer will be too thick or too thin, and the desired effect cannot be achieved, resulting in no benefit in ED. When the buckypaper thickness is too thin, it cannot form a coating and cannot restrain the silicon-based expansion. When the buckypaper thickness is too large, it will affect the energy density and cycle performance of the battery cell.

[0015] Preferably, the tensile strength of the buckypaper is 0.5-8 MPa.

[0016] Preferably, the electrical conductivity of the buckypaper is 500-1500 S / m.

[0017] If the tensile strength is too low, it is easy to break, and if the tensile strength is too high, it will have a strong impact on the softness of the buckypaper, which is not conducive to overmolding. If the conductivity is too low, it will affect the lithium ion conduction speed of the entire battery cell, and if it is too high, the system will not match, resulting in analysis.

[0018] Preferably, the buckypaper layer is formed by coating the outer surface of the silicon-carbon material with buckypaper through heat treatment.

[0019] Preferably, the heat treatment temperature is 800-900° C. If the heat treatment temperature is too high, the material structure will be destroyed and the structure will collapse, while if the temperature is too low, the coating structure cannot be formed. The temperature has a great influence on the residual silicon material.

[0020] In addition, the present invention also provides a negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on at least one side of the current collector, wherein the negative electrode active material layer is the above-mentioned silicon-based negative electrode material.

[0021] Preferably, the ratio of the thickness H of the buckypaper to the thickness D of the negative electrode active material layer is (0.75%-2.25%):1.

[0022] In addition, the present invention also provides a lithium ion battery, comprising a battery core wound by a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell encapsulating the battery core and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet. The thickness of the lithium ion battery is equal to the cumulative value of the thickness of all materials, and the thickness of the anode current collector is reduced compared with a conventional lithium ion battery.

[0023] If the anode current collector is 5μm copper foil and the lithium-ion battery is L layers, the thickness is reduced by d=5*Lμm (this thickness is calculated only for the theoretical thickness of the foil even if the influence of unevenness is ignored). If the overall thickness of the battery cell is H, the energy density can be increased by d / H*100%.

[0024] Compared with the prior art, the present invention has the following beneficial effects: the porous network structure and conductivity of buckypaper are conducive to the transmission of lithium ions and electrons, and the good softness provides space for the expansion of silicon, reduces the volume effect of silicon, and inhibits the expansion of the battery cell during the cycle. Compared with carbon nanotubes, buckypaper has uniform thickness, stronger stretchability, stronger elasticity, will not break easily, and better inhibits the expansion of silicon. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the structure of the silicon-based negative electrode material of the present invention.

[0026] Among them, 101 is porous silicon; 102 is a carbon coating layer; 103 is a buckypaper layer. DETAILED DESCRIPTION

[0027] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] According to the first aspect of the present application, the present application provides a silicon-based negative electrode material, whose structure includes porous silicon 101, a carbon coating layer 102 coating the porous silicon, and a buckypaper layer 103 coated on the outer surface of the carbon coating layer.

[0029] Among them, buckypaper has a large specific surface area, and has strength similar to that of thermally conductive graphite sheets, good electrical and thermal conductivity, and chemical stability.

[0030] Compared with conventional carbon nanotubes, the buckypaper layer can better alleviate the volume expansion effect of silicon, so that the silicon-carbon layer will not break the buckypaper layer and react with the electrolyte when expanding and contracting. This structure enhances the stability of the protective layer on the silicon surface, more effectively ensures the integrity of the silicon-carbon negative electrode, forms a more solid SEI film, and improves the cycle performance of the battery.

[0031] In some embodiments, the buckypaper includes one or more of carbon nanotube paper, carbon nanofiber paper, and carbon nanotube / fiber hybrid paper.

[0032] In some embodiments, the diameter of the buckypaper tube is 60-150 nm, for example, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, or 150 nm.

[0033] In some embodiments, the thickness of the buckypaper is 600-4500 nm, for example, 600 nm, 700 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 3000 nm, 3500 nm, 4000 nm, 4500 nm, wherein the preferred range of the buckypaper thickness is 600-1200 nm.

[0034] In some embodiments, the thickness of the buckypaper is H, the thickness of the carbon coating layer is d, and the ratio of the buckypaper thickness H to the carbon coating layer thickness d is (20-160): 1. For example, it can be 20:1, 50:1, 100:1, 120:1, 140:1, 160:1.

[0035] In some embodiments, the tensile strength of buckypaper is 0.5-8 MPa, for example, 0.5 MPa, 1.0 MPa, 1.5 MPa, 2.0 MPa, 2.5 MPa, 3.0 MPa, 3.5 MPa, 4.0 MPa, 4.5 MPa, 5.0 MPa, 5.5 MPa, 6.0 MPa, 6.5 MPa, 7.0 MPa, 7.5 MPa, 8.0 MPa.

[0036] In some embodiments, the conductivity of the buckypaper is 500-1500 S / m, for example, 500 S / m, 600 S / m, 700 S / m, 800 S / m, 900 S / m, 1000 S / m, 1100 S / m, 1200 S / m, 1300 S / m, 1400 S / m, 1500 S / m.

[0037] In some embodiments, the buckypaper layer 103 is formed by coating the outer surface of the silicon-carbon material with buckypaper through heat treatment.

[0038] In some embodiments, the temperature of the heat treatment is 800-900° C. For example, it may be 800° C., 850° C., or 900° C.

[0039] According to a second aspect of the present application, the present application provides a negative electrode sheet, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the above-mentioned silicon-based negative electrode material.

[0040] In some embodiments, the ratio of the thickness H of the buckypaper to the thickness D of the negative electrode active material layer is (0.75%-2.25%):1, for example, it can be 0.75%:1, 1.25%:1, 1.75%:1, 2.25%:1.

[0041] The present invention adopts silicon-based active materials coated with buckypaper to prepare current collector-free pole pieces, thereby improving the compaction density of negative pole pieces, reducing the overall thickness of the battery cell, and improving the energy density.

[0042] According to the third aspect of the present application, the present application provides a lithium-ion battery, comprising a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.

[0043] In some embodiments, the negative electrode sheet is rolled and slit, and then wound with a conventional positive electrode sheet and a separator to prepare a bare cell, and then a battery is manufactured through subsequent assembly, molding and testing steps.

[0044] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li aNi x Co y M z O 2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO 2 、LiNiO 2 、LiVO 2 、LiCrO 2 、LiMn 2 O 4 、LiCoMnO 4 , Li 2 NiMn 3 O 8 、LiNi 0.5 Mn 1.5 O 4 、LiCoPO 4 、LiMnPO 4 、LiFePO 4 、LiNiPO 4 ,LiC o FSO 4 , CuS 2 , FeS 2 、MoS 2 、NiS、TiS 2 The positive electrode active material may also be subjected to a modification treatment. The method for modifying the positive electrode active material should be known to those skilled in the art. For example, the positive electrode active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive electrode current collector is usually a structure or part for collecting current. The positive electrode current collector may be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.

[0045] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt can be LiPF used in high-temperature electrolytes. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6 , LiTFSI; it can also be LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; it may also be a chain carbonate, including DFC, DMC, or EMC; it may also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and a multifunctional additive.

[0046] Example 1

[0047] This embodiment 1 provides a silicon-based negative electrode material, including porous silicon 101 , a carbon coating layer 102 coating the porous silicon, and a buckypaper layer 103 coated on the outer surface of the carbon coating layer 102 .

[0048] Preparation of silicon-based negative electrode materials:

[0049] - 2g AlSi alloy powder and 250ml 1M dilute hydrochloric acid solution were magnetically stirred for 24 hours, rinsed with anhydrous ethanol for multiple times and vacuum dried at 60°C to obtain porous silicon microspheres. The above materials were placed in a tubular furnace, heated to between 700°C and 800°C in an inert gas Ar atmosphere, and ethylene gas was introduced for 30 minutes to obtain a porous silicon-carbon composite material.

[0050] Buckypaper is then used to perform secondary coating on the surface of the porous silicon-carbon composite material through heat treatment. The buckypaper has a tube diameter of 60nm, a thickness of 600nm, a tensile strength of 0.5MPa, a conductivity of 1000S / m, and a heat treatment temperature of 800°C; the ratio H of the buckypaper thickness to the carbon coating thickness is 20, and the ratio H of the buckypaper thickness to the thickness D of the negative electrode active material layer is 0.75%:1.

[0051] Preparation of negative electrode:

[0052] The silicon-based negative electrode material, dispersant and binder are mixed in a weight ratio of 97.7:1:1.3, hot pressed into a self-supporting film, and then cold pressed and stripped to obtain negative electrode sheets.

[0053] Preparation of lithium-ion batteries:

[0054] After rolling and slitting, the above-mentioned negative electrode sheet is wound with the conventional positive electrode sheet and separator to prepare a bare battery cell, and then manufactured into a battery through subsequent assembly, molding and testing processes for subsequent performance testing.

[0055] Example 2

[0056] Different from Example 1, the tube diameter of the buckypaper in this example is 150 nm.

[0057] The rest is the same as Example 1 and will not be described again here.

[0058] Example 3

[0059] Different from Example 1, the thickness of the buckypaper in this example is 1800 nm.

[0060] The rest is the same as Example 1 and will not be described again here.

[0061] Example 4

[0062] Different from Example 1, the tensile strength of the buckypaper in this example is 8 MPa.

[0063] The rest is the same as Example 1 and will not be described again here.

[0064] Example 5

[0065] Different from Example 1, the heat treatment temperature of the buckypaper in this example is 850°C.

[0066] The rest is the same as Example 1 and will not be described again here.

[0067] Example 6

[0068] Different from Example 1, in this example, the ratio H / d of the thickness of the buckypaper to the thickness of the carbon coating layer is 160.

[0069] The rest is the same as Example 1 and will not be described again here.

[0070] Example 7

[0071] Different from Example 1, in this example, the ratio H / D of the thickness of the buckypaper to the thickness of the negative electrode active material layer is 2.25%.

[0072] The rest is the same as Example 1 and will not be described again here.

[0073] Example 8

[0074] Different from Example 1, the tube diameter of the buckypaper in this example is 180 nm.

[0075] The rest is the same as Example 1 and will not be described again here.

[0076] Example 9

[0077] Different from Example 1, the tube diameter of the buckypaper in this example is 30 nm.

[0078] The rest is the same as Example 1 and will not be described again here.

[0079] Example 10

[0080] Different from Example 1, the thickness of the buckypaper in this example is 10000 nm.

[0081] The rest is the same as Example 1 and will not be described again here.

[0082] Embodiment 11

[0083] Different from Example 1, the tensile strength of the buckypaper in this example is 0.1 MPa.

[0084] The rest is the same as Example 1 and will not be described again here.

[0085] Example 12

[0086] Different from Example 1, the heat treatment temperature of the buckypaper in this example is 700°C.

[0087] The rest is the same as Example 1 and will not be described again here.

[0088] Embodiment 13

[0089] Different from Example 1, in this example, the ratio H / d of the thickness of the buckypaper to the thickness of the carbon coating layer is 10:1.

[0090] The rest is the same as Example 1 and will not be described again here.

[0091] Embodiment 14

[0092] Different from Example 1, in this example, the ratio H / D of the thickness of the buckypaper to the thickness of the negative electrode active material layer is 0.5%.

[0093] The rest is the same as Example 1 and will not be described again here.

[0094] Embodiment 15

[0095] Different from Example 1, in this example, the ratio H / D of the thickness of the buckypaper to the thickness of the negative electrode active material layer is 3%.

[0096] The rest is the same as Example 1 and will not be described again here.

[0097] Comparative Example 1

[0098] Different from Example 1, the negative electrode material used in this comparative example is a conventional negative electrode material without a carbon coating layer and a buckypaper layer.

[0099] The rest is the same as Example 1 and will not be described again here.

[0100] Comparative Example 2

[0101] Different from Example 1, this comparative example does not contain a buckypaper layer.

[0102] The rest is the same as Example 1 and will not be described again here.

[0103] Comparative Example 3

[0104] Different from Example 1, in this comparative example, there is no buckypaper layer outside the carbon coating layer, and the carbon nanotubes are conventional carbon nanotubes with a diameter of 15 nm.

[0105] The rest is the same as Example 1 and will not be described again here.

[0106] The following performance tests were performed on the batteries prepared in the examples and comparative examples:

[0107] (1) Swelling inhibition test: After the prepared battery is subjected to the same number of cycles, the thickness of the battery cell is tested, and the swelling inhibition is obtained by (thickness after test - initial thickness) / initial thickness*100%.

[0108] (2) Energy density improvement test: After the prepared battery is subjected to the same number of cycles, assuming that the current collector is Xμm, the number of battery layers is L, and the overall thickness of the battery is A, the energy density improvement = ((A / (A-((XH)*L / 1000)))-1)*100%.

[0109] Among them, the above performance test results are shown in Table 1 below.

[0110] Table 1

[0111]

[0112]

[0113] By comparing Examples 1-15 with Comparative Examples 1-3, it can be seen that when the diameter of the buckypaper tube and the thickness of the buckypaper are within a limited range, the thickness expansion rate can be effectively reduced and the energy density can be increased. If the diameter of the buckypaper tube is too large, the energy density will be reduced.

[0114] From the experimental data of Examples 1, 8-9, it can be seen that if the diameter of the buckypaper tube is greater than 150 mm, the energy density and cycle performance of the battery will be affected. In Example 9, although the energy density is theoretically improved, if the diameter of the buckypaper tube is less than 60 mm, the buckypaper film formed will be too thin to form a coating and cannot restrain the expansion of the silicon base.

[0115] It can be seen from the experimental data of Example 1 and Comparative Example 2 that when there is a buckypaper layer without a carbon coating layer, there is no obvious advantage in improving the energy density. The silicon-carbon material is not wrapped in a carbon layer, and is more likely to break during the cycle, and has no positive effect on increasing the thickness expansion.

[0116] It can be obtained from the experimental data of Example 1 and Comparative Example 3 that when there is no buckypaper outside the carbon coating layer and conventional carbon nanotubes are used for coating, there is no obvious advantage in thickness expansion when conventional carbon nanotubes are used for coating.

[0117] It can be seen from the experimental data of Examples 1, 7, 13-14 that when the ratio H / D of the thickness of the buckypaper to the thickness of the negative electrode active material layer is too small, the buckypaper film formed will be too thin to form a coating and unable to restrain the expansion of the silicon base; when the ratio H / D of the thickness of the buckypaper to the thickness of the negative electrode active material layer is too large, the energy density will be reduced.

[0118] In summary, the present invention provides a silicon-based negative electrode material, comprising porous silicon, a carbon coating layer coating the porous silicon, and a buckypaper layer coated on the outer surface of the carbon coating layer. If the buckypaper tube diameter is less than 60 mm, the buckypaper film thickness formed will be too thin to form a coating, and the silicon-based expansion will not be restrained. If the buckypaper tube diameter is greater than 150 mm, the energy density and cycle performance of the battery will be affected.

[0119] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material structure includes porous silicon, a carbon coating layer coating the porous silicon, and a buckypaper layer coating the outer surface of the carbon coating layer.

2. The silicon-based negative electrode material according to claim 1, characterized in that: The buckypaper includes one or more of carbon nanotube paper, carbon nanofiber paper, and carbon nanotube / fiber mixed paper.

3. The silicon-based negative electrode material according to claim 1, characterized in that: The tube diameter of the buckypaper is 60-150 nm.

4. The silicon-based negative electrode material according to claim 1, characterized in that: The buckypaper has a thickness of 600-4500 nm.

5. The silicon-based negative electrode material according to claim 1, characterized in that: The thickness of the buckypaper is H, the thickness of the carbon coating layer is d, and the ratio of the buckypaper thickness H to the carbon coating layer thickness d is (20-160):

1.

6. The silicon-based negative electrode material according to claim 1, characterized in that: The tensile strength of the buckypaper is 0.5-8 MPa.

7. The silicon-based negative electrode material according to claim 1, characterized in that: The electrical conductivity of the buckypaper is 500-1500 S / m.

8. The silicon-based negative electrode material according to claim 1, characterized in that: The buckypaper layer is formed by coating the outer surface of the silicon-carbon material with buckypaper through heat treatment.

9. The silicon-based negative electrode material according to claim 8, characterized in that: The temperature of the heat treatment is 800-900°C.

10. A negative electrode sheet, characterized in that: The invention comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises the silicon-based negative electrode material according to any one of claims 1 to 9.

11. The negative electrode sheet according to claim 10, characterized in that: The ratio of the thickness H of the buckypaper to the thickness D of the negative electrode active material layer is (0.75%-2.25%):

1.

12. A lithium ion battery, characterized in that: The negative electrode sheet according to claim 10 is included.

Citation Information

Patent Citations

  • Self-supporting flexible carbon nano-tube paper composite electrode material for lithium ion battery

    CN102593436A

  • Preparation method of silicon anode lithium-ion battery employing carbon nanotube paper as current collector

    CN105552379A

  • Silicon / graphene / carbon fiber composite cathode material and preparation method thereof

    CN105762337A

  • Self-supporting silicon / carbon nanotube composite negative electrode material and preparation method thereof

    CN111430690A

  • Preparation method of lithium-philic carbon nanotube paper and preparation method of composite metal lithium negative electrode

    CN112176771A